PENGARUH PENAYANGAN FILM SAYAP KECIL GARUDA DALAM UPAYA MENINGKATKAN MINAT MAHASISWA UNTUK BELAJAR MATA KULIAH PANCASILA - Safaruddin (Pojok Publisher, 2025)
This study aims to analyze the influence of film genre, film quality, and film reviews on interest in learning Pancasila courses. Using a quantitative approach, this study presents results based on numerical and statistical data to test the hypothesis objectively. This study involved measuring variables using a questionnaire instrument on respondents, then the data obtained were analyzed using the multiple linear regression method. The results of the analysis show that the three independent variables, namely the film genre “Sayap Kecil Garuda” (X1), the film quality “Sayap Kecil Garuda” (X2), and the film reviews “Sayap Kecil Garuda” (X3), simultaneously contributed 42.7% to the dependent variable, namely interest in learning Pancasila courses (Y). This figure is indicated by the coefficient of determination or R squared value of 0.427. This proves that films can be an effective tool in increasing interest in learning. The remaining 57.3% of interest in learning is influenced by other factors outside this research model, which are not included in the regression analysis. These findings demonstrate the great potential of visual media such as films in supporting character education and understanding of Pancasila values.